Integrative systematics of the genus Dondice Marcus, 1958 (Gastropoda, Nudibranchia, Myrrhinidae) in the Western Atlantic - García-Méndez, K.; Padula, V.; Valdés, Á. (Marine Biodiversity, 2022)
The evolutionary relationships of the nudibranch genus Dondice Er. Marcus, 1958, its hypothesized synonymy with Nanuca Er. Marcus, 1957, as well as its species-level diversity remain unresolved. Here, in order to assess the systematics of Dondice a molecular phylogenetic analysis based on cytochrome c oxidase I and 16S genes was carried out, including various representatives of the Myrrhinidae. As a result, Dondice is monophyletic and a valid genus, presenting morphological diagnostic features when compared to Nanuca. An integrative taxonomic approach focused on Western Atlantic Dondice occidentalis (Engel, 1925) and Dondice parguerensis Brandon & Cutress, 1985, including a broader geographic and morphological range of specimens, indicates that D. occidentalis constitutes a complex of six pseudocryptic species with geographically restricted ranges across the Western Atlantic, and D. parguerensis is a distinct, valid species. Dondice occidentalis s. str. is recognized as the species of the genus with the largest morphological variation, whereas the five new species, Dondice arianeae sp. nov., Dondice freddiemercuryi sp. nov., Dondice juansanchezi sp. nov., Dondice jupiteriensis sp. nov., and Dondice caboensis sp. nov. exhibit consistent morphological patterns, in agreement with molecular distinctiveness. Our study increases the number of known species of Dondice from four to nine and highlights the importance of addressing marine biodiversity within an integrative framework.